A Study on the Manufacturing of Molybdenum Pins for Electrodes - Lee, Jeong-Ick (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The molybdenum cup and molybdenum pin, which are the main materials of the molybdenum electrode used for the LCD BLU CCFL electrode, have not been developed in Korea and imported from Japan. In this paper, especially, research on prototype manufacturing and CAE analysis is performed to develop a molybdenum pin. In this research, to develop the manufacturing technology of molybdenum pin used for CCFL electrode of LCD BLU, development of linear processing technology, development of molybdenum wire surface treatment technology, development of wire cutting technology, production of molybdenum pin, design and fabrication of JIG and Fixture for inspection, molybdenum pin prototyping and analysis, and development of 100% molybdenum pin inspection technology. The development of molybdenum pins developed through this research can overcome Japan's technological level, which depends entirely on imports from Japan, and it is thought that the development will have a significant impact on the overall industry using molybdenum pins.